Optimizing Growth and Yield in Mulched Cotton Through Aerated Subsurface Drip Irrigation in Southern Xinjiang - Yuxi Zhang; Baolin Yao; Peining Niu; Zhu Zhu; Yan Mo; Fayong Li; Sanmin Sun (Agriculture)
This study investigates the impact of Aerated Subsurface Drip Irrigation (ASDI) on the growth and yield of mulched cotton, aiming to identify the optimal water-air combination pattern for ASDI in cotton cultivation. Conducted during 2021–2022, the experimental setup involved two aeration modes (aerated A1 and unaerated A0) and four irrigation quotas (W1, W2, W3, and W4), organized in a two-factor randomized block design resulting in eight distinct treatments. The findings revealed that ASDI significantly promoted soil moisture depletion from 0 to 40 cm during the cotton flowering and boll opening stages. Specifically, aerated A1 reduced soil water content by 5.84% to 7.83% during the flowering stage and 7.45% to 13.39% during the boll opening stage compared to unaerated A0. Additionally, both aerating and increasing irrigation quotas not only enhanced the cotton leaf area index (LAI) but also delayed leaf area decay, contributing to prolonged photosynthetic activity. Aerating also favorably influenced the distribution of above-ground biomass in cotton towards budding and boll stages, with the biomass share of buddings, flowers, and bolls averaging 62.98% under aerated conditions versus 62.27% under non-aerated conditions during the boll opening stage. Furthermore, aerating combined with increased irrigation quotas resulted in higher seed cotton yields, with aerated irrigation boosting yields by 1.79% in 2021 and 4.43% in 2022 compared to non-aerated irrigation. This approach also increased cotton’s water demand and average daily water consumption significantly (p < 0.01). Importantly, aerating improved IWUE, achieving 1.72 kg/m3 in 2021 and 1.62 kg/m3 in 2022 for ASDI, versus 1.69 kg/m3 and 1.57 kg/m3 for unaerated subsurface drip irrigation, respectively. In conclusion, from a water conservation and yield enhancement perspective, an irrigation quota of 337.4 mm during the reproductive stage under ASDI is recommended as an effective strategy for “one film three tubes and six rows” mulched cotton in Southern Xinjiang.